Research on environmental mutagenesis from young scientists – the open symposium of the Japanese Environmental Mutagen Society (JEMS) in 2017 - Masumura, Kenichi (Genes Environ, 2017)
The open symposium of the Japanese Environmental Mutagen Society (JEMS) titled, “Research on Environmental Mutagenesis from Young Scientists,” was held at Kokusai Kenkyu Koryu Kaikan, the Foundation for Promotion of Cancer Research, in Tokyo on June 10, 2017. The aim of this symposium was to provide an opportunity to present the research activities of young scientists in the important field of environmental mutagenesis and genetic toxicology and inform JEMS activities to the participants. The organizers reported the symposium summary.